COVID-19 cases, vaccination, and SARS-CoV-2 in wastewater: insights from a Brazilian municipality - Mariana Aparecida de Freitas Abreu; Bruna Coelho Lopes; Paula Peixoto Assemany; Aline dos Reis Souza; Luciene Alves Batista Siniscalchi (IWA Publishing, 2024)
Vaccines combatting COVID-19 demonstrate the ability to protect against disease and hospitalization, and reduce the likelihood of death caused by SARS-CoV-2. In addition, monitoring viral loads in sewage emerges as another crucial strategy in the epidemiological context, enabling early and collective detection of outbreaks. The study aimed to monitor the viral concentration of SARS-CoV-2 in untreated sewage in a Brazilian municipality. Also, it attempted to correlate these measurements with the number of clinical cases and deaths resulting from COVID-19 between July 2021 and July 2022. SARS-CoV-2 viral RNA was quantified by RT-qPCR. Pearson's correlation was performed to analyze the variables' relationship using the number of cases, deaths, vaccinated individuals, and viral concentration of SARS-CoV-2. The results revealed a significant negative correlation (p < 0.05) between the number of vaccinated individuals and the viral concentration of SARS-CoV-2, suggesting that after vaccination, the RNA viral load concentration was reduced in the sample population by the circulating concentration of wastewater. Consequently, wastewater monitoring, in addition to functioning as an early warning system for the circulation of SARS-CoV-2 and other pathogens, can offer a novel perspective that enhances decision-making, strengthens vaccination campaigns, and contributes to authorities establishing systematic networks for monitoring SARS-CoV-2. HIGHLIGHTS The presence of SARS-CoV-2 was detected in 100% of the wastewater samples.; Wastewater SARS-CoV-2 concentration negatively correlated with vaccinated individuals.; Wastewater-based epidemiology is a tool for the monitoring of virus during vaccination campaigns.;